2020
DOI: 10.1101/2020.07.24.220160
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protective Plant Immune Responses are Elicited by Bacterial Outer Membrane Vesicles

Abstract: SummaryBacterial outer membrane vesicles (OMVs) perform a variety of functions in bacterial survival and virulence. In mammalian systems, OMVs activate immune responses and have been exploited as vaccines. However, little work has focused on the role that OMVs play during interactions with plant hosts. Here we report that OMVs from the pathogenic Pseudomonas syringae and the beneficial Pseudomonas fluorescens activate plant immune responses that protect against bacterial and oomycete pathogens. OMVs from these… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(30 citation statements)
references
References 120 publications
4
25
1
Order By: Relevance
“…These results suggest that the immunogenic activities of the EVs, but not a longer-term trade-off with growth, may be relevant in their interaction with plants. In contrast to our results, McMillan et al reported significant seedling growth repression in response to Pto DC3000 EVs (McMillan et al , 2020). This disparity in results may be due to several factors, including differences in the growth conditions of both the bacterial cultures and the A. thaliana seedlings, the type of biochemical isolation of EVs and vesicle dose.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…These results suggest that the immunogenic activities of the EVs, but not a longer-term trade-off with growth, may be relevant in their interaction with plants. In contrast to our results, McMillan et al reported significant seedling growth repression in response to Pto DC3000 EVs (McMillan et al , 2020). This disparity in results may be due to several factors, including differences in the growth conditions of both the bacterial cultures and the A. thaliana seedlings, the type of biochemical isolation of EVs and vesicle dose.…”
Section: Discussioncontrasting
confidence: 99%
“…4A, S4A). Thus, the immunogenic potential of Pto DC3000 EVs is sufficient to restrict bacterial colonization, consistent with recent observations (McMillan et al , 2020). Since MAMP treatment mediates anti-bacterial protection through the induction of plant immune reactions (Zipfel et al , 2004), we next evaluated defence gene expression to EV treatment using pFRK1::GUS reporter lines (Kunze et al , 2004).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations